EDUCATION ACCORDING TO THE CONCEPT OF THE Q.S. AL-BAQARAH verse 31 - Putra Mahendra Gunawan Nasution (Universitas Muhammadiyah Surabaya, 2023)
ABSTRACTThis study aims to understand the explanation of education according to the Qur'an which refers to Q.S. Al-Baqarah: 31. This research is a library research. The method and focus on this analysis were used in analyzing the data. This research method uses a qualitative descriptive approach in the form of words or language by utilizing various scientific methods. This study discusses education according to Q.S. Al-Baqarah: 31, namely Allah has taught Adam (as) the names of all objects, then Allah showed the angels, saying,